2022
DOI: 10.3389/ti.2022.10880
|View full text |Cite
|
Sign up to set email alerts
|

Interventions After First Post-Transplant Cutaneous Squamous Cell Carcinoma: A Proposed Decision Framework

Abstract: Cutaneous squamous cell carcinoma (CSCC) is a major cause of morbidity and mortality after organ transplant. Many patients subsequently develop multiple CSCC following a first CSCC, and the risk of metastasis and death is significantly increased compared to the general population. Post-transplant CSCC represents a disease at the interface of dermatology and transplant medicine. Both systemic chemoprevention and modulation of immunosuppression are frequently employed in patients with multiple CSCC, yet there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…This study found an incidence rate ratio (IRR) of 0.44 (p = 0.03, 95% CI = 0.21-0.92) when SOTRs were switched from cyclosporine to tacrolimus, as well as an IRR of 1.66 (p = 0.01, 95% CI = 1.16-2.36%) with azathioprine compared to an IRR of 0.78 with mycophenolate (p = 0.18, 95% CI = 0.54-1.12) [9]. Additionally, transition from azathioprine to mycophenolate appears to reduce the risk of developing a first cutaneous SCC post solid organ transplantation with mycophenolate having an IRR of 0.49 (p = 0, 95% CI = 0.32-0.75) compared to azathioprine in this setting [9][10][11].…”
Section: Immunosuppressionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study found an incidence rate ratio (IRR) of 0.44 (p = 0.03, 95% CI = 0.21-0.92) when SOTRs were switched from cyclosporine to tacrolimus, as well as an IRR of 1.66 (p = 0.01, 95% CI = 1.16-2.36%) with azathioprine compared to an IRR of 0.78 with mycophenolate (p = 0.18, 95% CI = 0.54-1.12) [9]. Additionally, transition from azathioprine to mycophenolate appears to reduce the risk of developing a first cutaneous SCC post solid organ transplantation with mycophenolate having an IRR of 0.49 (p = 0, 95% CI = 0.32-0.75) compared to azathioprine in this setting [9][10][11].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…These clinical findings are supported by transitional research showing that cutaneous SCC in SOTRs taking azathioprine show unique mutational signatures caused by UVA absorption by DNA [ 7 , 8 ]. While azathioprine is now less commonly used as a primary immunosuppression regimen for SOTRs, it is still used in patients who are intolerant to mycophenolate therapy or who may be planning to become pregnant [ 9 ].…”
Section: Immunosuppressionmentioning
confidence: 99%
See 2 more Smart Citations